Кластер у секторальній відбудові освіти України - Колісніченко, Наталя Миколаївна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Обґрунтовано роль і значення кластеру та кластеризації у секторальній відбудові освіти України; уточнено термін «кластер», ідентифіковано основні характеристики кластерів; досягнення необхідної «критичної маси» у розмірі кластера; життєздатність кластерів; залучення до інноваційного процесу. Визначено поняття «освітній кластер» («освітньо-науковий кластер») та сформульовано характерні особливості кластеризації в освіті. Зазначено, що у практичному плані кластерний підхід в освіті реалізується в управлінні освітніми кластерами. Виділено рівні кластеризації в освіті: рівень окремих компетенцій (кластер освітніх компетенцій); рівень освітньої програми; рівень закладу освіти; рівень території/територіальної громади. Досліджено регіональний соціокультурний освітній кластер.

The role and significance of the cluster and clustering in the sectoral reconstruction of education in Ukraine are substantiated; the term "cluster" has been clarified, main characteristics of clusters have been identified; achieving the necessary "critical mass" in the size of the cluster; viability of clusters; involvement in the innovation process. The concept of "educational cluster" ("educational-scientific cluster") is defined and the characteristic features of clustering in education are formulated. It is noted that in practical terms, the cluster approach in education is implemented in the management of educational clusters. Levels of clustering in education are highlighted: level of individual competencies (cluster of educational competencies); the level of the educational program; the level of the educational institution; level of territory/territorial community. The regional socio-cultural educational cluster was studied.
Cluster in sectoral recovery of Ukraine's education
Keywords: публічне управління; кластер; соціальні послуги; людський капітал; соціальні інвестиції; освітній кластер; управління кластерами; інноваційність; public administration; cluster; social services; human capital; social investments; educational cluster; cluster management; innovation